MANAJEMEN SUMBER DAYA INSANI (Konsep Dasar Perencanaan dan Analisis Jabatan di Perbankan Syariah) - nur rahmawati (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACT In this globalization era, there are many issues in the development of global competition, including unlimited free competition in a particular region or country. This freedom to do business has become the demands and needs of the world community from any angle. So the existence of Human Resource Management (MSDI) is very important for Islamic banking in managing and using Human Resources that function productively, effectively, and efficiently to be able to survive and compete in the global arena.Human Resources is an infinite gift from Allah SWT, but if human resources are not managed properly, then an institution or company, even the country will be left behind and could be down. An institution, company and country that is unable to progress, the problem is not the quality of the Human Resources, but on the quality of Human Resources Management, how many bad the Human Resources there, if managed properly, it will produce Â institutions, companies and developed countries. To that end, human resources must be planned carefully, must be analyzed in depth related to positions(jobs) in accordance with the SDI field owned by a sharia banking, so that what is called the right man in one place wasformed.Keywords : Management, Planning, Job Analysis and Banking